Employee commitment in Ghanaian healthcare: a multi-factor analysis - Emmanuel Erastus Yamoah (Business, Management and Economics Engineering)
Purpose – The study investigates the factors influencing organizational commitment among employees at a Municipal Health Directorate (MHD) in Ghana. It focuses on identify- ing key organizational and individual factors that drive commitment and examining potential gender differences.